Population Distribution of Rats (Rattus argentiventer) and the Damage Intensity on Rice and Other Crops in Pleret, Yogyakarta, Indonesia - Brotodjojo, RR Rukmowati; Lazuardi, Ikhsan; Suprihanti, Antik (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2023)
Rice field rats is one of the main pests of rice in Indonesia and other Asian countries that can cause a crop failure. The availability food sources might affect the rat foraging in the field. The research aimed to determine the distribution of rat population and their nests in the field with different crop and to examine the level of crop damage caused by rats. The research was conducted from January to April 2023 in Pleret district, Yogyakarta, Indonesia. The 1000 m2 TBS (Trap Barrier System) was installed in the middle of the 225 ha observation area to trap rats. Crop damage inside TBS was observed using a diagonal sampling method. Crop damage outside TBS was observed using the line transect method in the 4 cardinal directions with a distance of 250m, 500m, and 750m from TBS. Rat nest’s locations were mapped using GPS. The results showed that the number of rats trapped was low in the early and late stage of rice growth and peaked when the rice aged 12 weeks after planting (WAP). Rice crop damage inside TBS occurred when rice entered 12 WAP. There was no damage on rice crops around the TBS. Rats also attacked corn and sugarcane which caused heavy damage to these crops. There were 157 active holes found in 225ha observation area and they mostly were found in rice field bunds, irrigation embankments, and vacant land. This study implied that understanding the distribution of rat’s population and their nest will support the rat control.